STRATEGI KOMUNIKASI PENINGKATAN ENGAGEMENT (LIKE, SHARE, DAN COMMENT) TIKTOK @UNIVERSITAS DIPONEGORO DAN INSTAGRAM @UNDIP.OFFICIAL MELALUI PRODUKSI KONTEN VIDEO SEBAGAI CREATIVE DAN PROGRAM DIRECTOR - Muhammad Aziz Mirza Harisma; Agus Naryoso (Interaksi Online, 2026)
The growth of social media has reshaped digital communication patterns, especially inhow educational institutions distribute information. Diponegoro University leverages socialmedia, particularly through the @undip.official account, as a platform for publiccommunication, information sharing, and strengthening its institutional image. However, itscontent management still requires further optimization to improve audience engagement. Thisprofessional project focuses on implementing a digital communication strategy by producingvideo content on TikTok and Instagram (@undip.official) to increase engagement levels. Theprocess was conducted in three main stages—pre-production, production, and postproduction—while applying the AISASmodel (Attention, Interest, Search, Action, andShare) as the strategic framework. Within this project, the author took responsibility for managing all stagesof content production, including pre-production, production, and post-production, aswell as conducting target audience analysis, developing and organizing content matrices andmedia recommendations, evaluating content performance, and coordinating the publicationprocess. The results show a significant increase in content output, from 45 to 75 pieces,accompanied by higher audience engagement in the form of likes, comments, and shares. Thisindicates that optimizing digital communication strategies through creative content canenhance the effectiveness of social media as a tool for institutional communication.